Existential reflection and morality - Sopcak, Paul; Kuiken, Don; Douglas, Shawn (Frontiers in Communication, 2022)
This paper presents a series of three studies describing how reading literature promotes empathy and moral outcomes. We add three contrasts to this field of empirical study: a) an explanatory and interpretative form of reading engagement (Integrative Comprehension) is contrasted with an expressive and explicative form of aesthetic reading engagement (Expressive Enactment); b) within that contrast, a passively explanatory and interpretive form of cognitive perspective-taking is distinguished from an actively expressive and explicative form of empathy; and c) as potential effects of these contrasting forms of reading engagement, we distinguish local forms of moral outcome (involving changes in attitude toward a specific group or outgroup) from global forms of moral outcome (involving an expansive, self- and other-directed respect for humanity). These contrasts are clarified and contextualized within existential-phenomenological discussions of sense-giving lived experience, agency, and morality. In conclusion, we offer a framework that specifies the potential impact on well-being of a form of literary reading that involves existential reflection, especially as conceived within the emerging field of existential positive psychology.